2016
DOI: 10.1051/0004-6361/201526297
|View full text |Cite
|
Sign up to set email alerts
|

Inferring heat recirculation and albedo for exoplanetary atmospheres: Comparing optical phase curves and secondary eclipse data

Abstract: Context. Basic atmospheric properties, such as albedo and heat redistribution between day-and nightsides, have been inferred for a number of planets using observations of secondary eclipses and thermal phase curves. Optical phase curves have not yet been used to constrain these atmospheric properties consistently. Aims. We model previously published phase curves of CoRoT-1b, TrES-2b, and HAT-P-7b, and infer albedos and recirculation efficiencies. These are then compared to previous estimates based on secondary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 82 publications
(287 reference statements)
3
18
0
Order By: Relevance
“…No clear signs of clouds have been found, although for HAT-P-7b, results seem to indicate a small but not statistically very significant asymmetry consistent with previous phase curve analyses by von Paris et al (2016). There are several reasons for this.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…No clear signs of clouds have been found, although for HAT-P-7b, results seem to indicate a small but not statistically very significant asymmetry consistent with previous phase curve analyses by von Paris et al (2016). There are several reasons for this.…”
Section: Discussionsupporting
confidence: 81%
“…This would suggest that the trailing limb appears slightly larger (of the order of a couple of scale heights). Such a result is actually consistent with the analysis of von Paris et al (2016) who found that the asymmetric phase curve of HAT-P-7b is more likely due to an asymmetry in scattering properties than due to a thermal offset, contrary to previous studies (e.g., Esteves et al 2015). However, given that the constraints are very weak, such a conclusion appears to be only tentative.…”
Section: Planetsupporting
confidence: 89%
See 1 more Smart Citation
“…These reflected light signatures complement the thermal structure and orbital information inferred from phase variations and secondary eclipses detected in the infrared (Harrington et al 2006;Knutson et al 2007;Kane & Gelino 2011a;Demory et al 2016). Secondary eclipse observations enable the measurement of atmospheric temperatures that are critical in modeling exoplanet atmospheres and interiors (Line & Yung 2013;von Paris et al 2016;Fortney et al 2019). Furthermore, the additional phase variation components of ellipsoidal variations and Doppler beaming can be used to distinguish between stellar and planetary companions to the host star (Drake 2003;Kane & Gelino 2012a).…”
Section: Phase Variations and Secondary Eclipsesmentioning
confidence: 77%
“…Both the optical and IR phase curves of HAT-P-7 b have been studied previously 5,6,9,[11][12][13] . The optical phase curve exhibits a significant fraction of thermal emission (potentially as high as 77% 6 ), due to the high temperature of the planet.…”
Section: Main Textmentioning
confidence: 99%